Positive youth development through gig economy among food panda delivery services in Malacca, Malaysia - Md Yusof, Atikah; Arshad, Mohd Mursyid; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2022)
Food delivery services have increased in popularity as a result of the rapid development of globalisation via internet facilities, since this service is a mean that consumers use to meet their basic needs and as a means of generating revenue for people who work in the gig economy. However, in Malaysia's economic sector, the phrase relating to these gig workers is still ambiguous, and comprehensive statistics on such data is still lacking at the policymaker level. This lack of data leads to a lack of detailed knowledge on their motives and needs, who is involved, how many hours they work and their voices in this field of work, which is likely to result in less effective policy formation. Furthermore, previous research on gig workers have only discussed it in broad terms, instead of focusing specifically on millennials, particularly youth, individual character, and interests of Gig workers. Gig jobs are predominantly populated by the younger generation, particularly students, the jobless, and new grads who are eager for employment but aren't worried about saving for retirement. Integrity and self-improvement, on the other hand, might help to the development of a positive personality in them throughout this period of work, even if they are unaware of it. This research used a qualitative case study. Document analysis and semi-structured interviews with four Foodpanda volunteers served as primary informants were used to collect data. As a result, the purpose of this research is to find out what drives young people to take part in food delivery services as part of their gig employment, and how the experience acquired can help to Positive Youth Development. According to the study's findings, there are four main motivations that motivate youths to participate in this service: meeting personal needs, psychology, developing social networks, and providing a flexible work system that ultimately strengthens self-development in a more positive direction through the development of 5C elements in Positive Youth Development (PYD).